Periplasmic Cytochrome c(3) of Desulfovibrio vulgaris Is Directly Involved in H(2)-Mediated Metal but Not Sulfate Reduction - Elias, Dwayne A. (American Society for Microbiology, 2004)
Kinetic parameters and the role of cytochrome c(3) in sulfate, Fe(III), and U(VI) reduction were investigated in Desulfovibrio vulgaris Hildenborough. While sulfate reduction followed Michaelis-Menten kinetics (K(m) = 220 μM), loss of Fe(III) and U(VI) was first-order at all concentrations tested. Initial reduction rates of all electron acceptors were similar for cells grown with H(2) and sulfate, while cultures grown using lactate and sulfate had similar rates of metal loss but lower sulfate reduction activities. The similarities in metal, but not sulfate, reduction with H(2) and lactate suggest divergent pathways. Respiration assays and reduced minus oxidized spectra were carried out to determine c-type cytochrome involvement in electron acceptor reduction. c-type cytochrome oxidation was immediate with Fe(III) and U(VI) in the presence of H(2), lactate, or pyruvate. Sulfidogenesis occurred with all three electron donors and effectively oxidized the c-type cytochrome in lactate- or pyruvate-reduced, but not H(2)-reduced cells. Correspondingly, electron acceptor competition assays with lactate or pyruvate as electron donors showed that Fe(III) inhibited U(VI) reduction, and U(VI) inhibited sulfate loss. However, sulfate reduction was slowed but not halted when H(2) was the electron donor in the presence of Fe(III) or U(VI). U(VI) loss was still impeded by Fe(III) when H(2) was used. Hence, we propose a modified pathway for the reduction of sulfate, Fe(III), and U(VI) which helps explain why these bacteria cannot grow using these metals. We further propose that cytochrome c(3) is an electron carrier involved in lactate and pyruvate oxidation and is the reductase for alternate electron acceptors with higher redox potentials than sulfate.